Converting molecular layer deposited alucone films into Al2O3/alucone hybrid multilayers by plasma densification. Issue 4 (22nd December 2020) - Santo Domingo Peñaranda, Juan; Nisula, Mikko; Vandenbroucke, Sofie S. T.; Minjauw, Matthias M.; Li, Jin; Werbrouck, Andreas; Keukelier, Jonas; Pitillas Martínez, Andrea I.; Dendooven, Jolien; Detavernier, Christophe
Abstract : Alucones are one of the best-known films in the Molecular Layer Deposition (MLD) field. In this work, we prove that alucone/Al2 O3 nanolaminate synthesis can be successfully performed by alternating alucone MLD growth with static O2 plasma exposures. Abstract : Alucones are one of the best-known films in the Molecular Layer Deposition (MLD) field. In this work, we prove that alucone/Al2 O3 nanolaminate synthesis can be successfully performed by alternating alucone MLD growth with static O2 plasma exposures. Upon plasma treatment, only the top part of the alucone is densified into Al2 O3, while the rest of the film remains relatively unaltered. X-ray reflectivity (XRR) and X-ray photoelectron spectroscopy (XPS) depth profiling show that the process yields a bilayer structure, which remains stable in air. Fourier-transform infrared spectroscopy (FTIR) measurements show that Al2 O3 features are generated after plasma treatment, while the original alucone features remain, confirming that plasma treatment results in a bilayer structure. Also, an intermediate carboxylate is created in the interface. Calculations of Al atom density during plasma exposure point towards a partial loss of Al atoms during plasma treatment, in addition to the removal of the glycerol backbone. The effect of different process parameters has been studied. Densification at the highest temperature possible (200 °C) has the best alucone preservation without hindering its thermal stability. In addition, operating at the lowest plasma power is found the most beneficial for the film, but there is a threshold that must be surpassed to achieve successful densification. About 70% of the original alucone film thickness can be expected to remain after densification, but thicker films may result in more diffuse interfaces. Additionally, this process has also been successfully performed in multilayers, showing real potential for encapsulation applications.